Comparison of antibiotic regimens in preterm premature rupture of membranes: neonatal morbidity and 2-year follow-up of neurologic outcome. (17th September 2017) - Chang, Kylie Hae-Jin; Kim, Hyun-Joo; Yu, Hee Joon; Lee, Jeehun; Kim, Jung-Sun; Choi, Suk-Joo; Oh, Soo-young; Roh, Cheong-Rae; Kim, Jong-Hwa
Abstract: Objectives : The objective of this study was to compare neonatal morbidity and neurologic outcome at 2 years between groups treated with antibiotics regimens consisting clarithromycin and erythromycin in preterm premature rupture of the membranes (pPROM) patients delivered before 32 weeks of gestation. Methods : This was a retrospective study comparing neonatal morbidity as primary outcome measures and the neurological outcome at 2 years as secondary outcome. Results : A total of 166 women were included: 80 treated with erythromycin and 86 treated with clarithromycin. The median gestational age at delivery was greater in clarithromycin group ( p  = 0.005). There was no significant difference in latency ( p  = 0.77). The incidence of histological chorioamnionitis was significantly lower in clarithromycin group ( p  = 0.004). By multivariable analysis adjusting confounding variables, the incidence of bronchopulmonary dysplasia and intraventricular hemorrhage (≥Grade 3) was lower in clarithromycin group (BPD; OR 0.34, 95% CI [0.13–0.90]), IVH; OR 0.23, 95% CI [0.06–0.91], respectively). Other morbidities and neurologic outcome at 2 years' corrected age showed no statistically significant difference between two groups. Conclusion : We suggest that clarithromycin-based regimen may be worth considering as an alternative choice of erythromycin in pPROM patients.